Türk milletini, Türkiye cumhuriyeti Devletini, devletin kurum ve organlarını aşağılama suçu (TCK m. 301) - Yıldırım, Mustafa Zeki (My University, 2012)
Türk Milletini, Türkiye Cumhuriyeti Devletini, Devletin Kurum Ve Organlarını Aşağılama Suçu (TCK m. 301) Bu çalışma Ceza hukuku teori ve ilkeleri çerçevesinde 5237 sayılı Türk Ceza Kanunun 301. maddesinin incelenmesidir. Suçun unsurları ve suçun özel görünüş şekilleri açıklanmıştır. Çalışmada; değiştirilen ve yeni kavramlar getirilen madde metni analiz edilip, yeni halinin sınırları tespit edilmeye çalışılmıştır. Madde de değişmeyen kısımların yeniden yorumlamanın yanında, değişikliğe uğrayan “Türklük” “Türk Milleti,” “Cumhuriyet” “Türkiye Cumhuriyeti Devleti”, “Tahkir Ve Tezyif” “Aşağılama” gibi kavramların farklılıkları incelenmiş, mukayeseli hukuktaki benzer düzenlemelere yer vermenin yanında yargı kararlarıyla da konunun vuzuha kavuşmasına gayret edilmiştir. Hakkın icrası kapsamında maddede yer alan eleştiri hakkı ve düşünce özgürlüğü detaylı sayılabilecek bir şekilde incelenmiştir. Kendi içinde AİHM kararların anlamı ve önemi üzerinde durulmuştur. Özellikle siyasiler ve devlet mevzubahis olduğunda düşünce özgürlüğünün alanının daha geniş olduğunu belirten AİHM kararlarına vurgu yapılmıştır. Bu konunun AİHM’nin istikrar kazanmış genel bir yaklaşımı olduğu belirtilmiştir. izin şartının 301. madde açısından önemine dikkat çekilmiş, Adalet Bakanı kamu yararı açısından değerlendirirken zorunluluk olmadıkça izin yetkisini kullanmaması gerektiği üzerinde durulmuştur.

The crime of denigrating the Turkish nation, the Republic of Turkey, the institutions and the organs of the State (Turkish Penal Code, Article 301) This study is aimed at the analysis of the Article 301 of the Turkish Penal Code, Law No. 5237, in line with the theory and principles of the criminal law. Here, the elements of the crime, and also of the special aspects of the respective crime have been explored. The concepts introduced by the recent amendments to the law have been analyzed, and the scope of the crime has been attempted to be re-delineated accordingly. . Along with the re-interpretation of the concepts which have not been amended, the differences among the amended concepts in the Article introduced by the last amendment, such as the “Turkishness”, “Turkish Nation”, “The Republic of Turkey”, “Insulting and denigrating”, and “denigration” have also been sorted out; morover, the efforts have been made to elucidate the subject through the analysis of the the judicial decisions and judgments, along with the consideration of the similar laws existed in the comparative law to the study. The right to critize (government) which should be comprised by the concept of ‘exercise of a right’, and the freedom of thought have been clarified in almost a detailed way. The study also focuses on the meaning and the importance of the jurisprudence of the European Court of Human Rights (EchR) in its specific contex. Here, the emphasise is given in particular to the decisions and judgments of the EchR, whereby the freedom of expression has been given more latitude in the cases where the government or the politicians are involved than the cases in which the ordinary persons are involved only. It is argued in the study that the Court has on every occasion maintained consistently this approach to the subject. Furthermore, the importance of the prior permission by the Ministry of Justice for the prosecutions to be initiated based on the Article 301 has been emphasized in the study, and been evinced also that the Ministry of Justice should not permit the prosecution under the Article unless a conclusion that a compelling public interest exists, drawing through the appraisal of the case.
Keywords: Suçlar_Hukuk; Türk Ceza Kanunu